2017
DOI: 10.1016/j.coviro.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkeys for a nonhuman primate model of cytomegalovirus infections

Abstract: Human cytomegalovirus (HCMV) is the leading opportunistic viral infection in solid organ transplant patients and is the most common congenitally transmitted pathogen worldwide. Despite the significant burden of disease HCMV causes in immunosuppressed patients and infected newborns, there are no licensed preventative vaccines or effective immunotherapeutic treatments for HCMV, largely due to our incomplete understanding of the immune correlates of protection against HCMV infection and disease. Though CMV specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 89 publications
(75 reference statements)
0
49
0
Order By: Relevance
“…Yet, congenital virus transmission can be modeled using both guinea pigs and nonhuman primate models [7,24]. In particular, rhesus macaques and their corresponding endogenous rhesus CMV (RhCMV) are a highlyrelevant model for understanding adult/fetal HCMV pathogenesis [25,26] and congenital infection [9,27], as the physiology/immunology of rhesus monkey pregnancy is highly analogous to humans [25], there is extensive protein homology between RhCMV and HCMV [28], and certain mechanisms of viral immune evasion are conserved between these viruses [29,30]. Previously, our group demonstrated that the depletion of CD4 + T cells followed by intravenous RhCMV inoculation of seronegative pregnant monkeys resulted in consistent RhCMV congenital infection and a high rate of fetal loss [24].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, congenital virus transmission can be modeled using both guinea pigs and nonhuman primate models [7,24]. In particular, rhesus macaques and their corresponding endogenous rhesus CMV (RhCMV) are a highlyrelevant model for understanding adult/fetal HCMV pathogenesis [25,26] and congenital infection [9,27], as the physiology/immunology of rhesus monkey pregnancy is highly analogous to humans [25], there is extensive protein homology between RhCMV and HCMV [28], and certain mechanisms of viral immune evasion are conserved between these viruses [29,30]. Previously, our group demonstrated that the depletion of CD4 + T cells followed by intravenous RhCMV inoculation of seronegative pregnant monkeys resulted in consistent RhCMV congenital infection and a high rate of fetal loss [24].…”
Section: Introductionmentioning
confidence: 99%
“…HCMV preclinical vaccine development is hindered by the fact that small animal models poorly represent host-pathogen biology and mechanisms of disease pathogenesis [26, 27]. We chose to test immunogenicity in rabbits because we previously demonstrated that vaccination can elicit antibodies with both neutralizing and non-neutralizing in vitro functionality [17].…”
Section: Discussionmentioning
confidence: 99%
“…The strict tropism of HCMV to humans urged the study of homologous cytomegaloviruses (CMVs) in other animal species. There is vast literature regarding murine CMV (MCMV) and also several reports about rhesus monkey CMV (RhCMV) models (for a brief overview, see Table 1) [20][21][22][23][24][25][26][27][28]. This wealth of work contributes extensively to the understanding of basic aspects of the interactions between CMV and the host.…”
Section: Mouse Models Of Hcmv Infections and Human Immune Responsesmentioning
confidence: 99%